Digitalization of National Health Insurance (JKN) claims and hospital operational efficiency in BPJS Kesehatan partner hospitals: A Systematic Literature Review with Conditional Meta-Analysis - Shafitri Nire pangestika; Ernawati Ernawati; Rita Rahmawati; Lazuardi Fatahilah Hamdi; Cahyu Septiwi (Jurnal Keperawatan, 2026)
Introduction: Digitalization of National Health Insurance (JKN) claims is a major administrative health reform in Indonesia; since JKN's 2014 launch, transaction volumes have exceeded 1.37 million claims per day, straining conventional paper-based systems. No prior review has systematically synthesized digitalization's cumulative impact on operational efficiency in BPJS Kesehatan partner hospitals.Objectives: This study aimed to synthesize evidence on the relationship between JKN claim digitalization and hospital operational efficiency, and to estimate the pooled effect on claim cycle time where study homogeneity permits.Methods: A Systematic Literature Review using the PRISMA 2020 protocol searched five databases—PubMed/MEDLINE, Scopus, Web of Science, Google Scholar, and Garuda—for publications from January 2014 to December 2024. Quality was assessed using STROBE, CASP, MMAT, and AMSTAR 2, and a conditional random-effects meta-analysis targeted claim cycle time, the outcome with adequate homogeneity across studies.Results: From 438 records, 25 articles met the inclusion criteria, reporting six efficiency dimensions: claim cycle time, first-pass rejection rate, cash flow/days in accounts receivable, staff utilization, ICD coding accuracy, and administrative cost per claim. Meta-analysis of 11 homogeneous studies showed a pooled mean reduction in claim cycle time of 19.6 days (95% CI: 14.2–25.1) post-implementation, with high heterogeneity (I² = 78.4%).Conclusions: The integrated TAM-UTAUT-RBV framework explains this evidence: systems combining automated bridging with real-time validation outperform partial digitalization, with human resource competency and IT infrastructure as key contextual factors. Findings carry implications for future research and for BPJS Kesehatan, the Ministry of Health, and hospitals in prioritizing capacity-adjusted digitalization strategies.